The God of Jesus Christ - Kasper, Walter, 1933- (Continuum International Pub., 2012)
Kasper is a master synthesiser, and his display of erudition alone makes this book a worthy read and an invaluable resource for questions of God and Trinity. Using admittedly polemical language, he calls for a 'theological theology' which makes the explanation of the confession of the triune God its first priority, not only for speculative but also for pastoral reasons. This is the reissue of a theological work of considerable importance for which Cardinal Kasper has written an entirely new introduction taking modern developments in theology fully into account.